HEALTH STATUS AND HEALTH SERVICE UTILIZATION IN RETIREMENT - Cahya Edi Prastyo; Ascobat Gani (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Demographic Transition leads to changes in disease patterns, affecting retired workers and their spouses in the mining industry as they transition into retirement. This study examines the health status of retirees and their spouses and its impact on health service utilization. This descriptive cross-sectional study gathered data from 1644 retirees and their spouses receiving Employer Sponsored retiree health services in Indonesia in 2023. The study revealed that 65.9% of respondents had a history of chronic diseases, with 35.02% having more than one chronic disease. Most respondents of retired workers were men (90.93%), and most spouses were women (78.4%). Chronic diseases were higher among women. Health service utilization increased with age and was higher among those with a history of chronic diseases. Those with chronic diseases utilized health services more frequently than those without, indicating a 3.4 times increase in utilization. Retirees are susceptible to chronic diseases and multimorbidity, with female spouses being particularly vulnerable. Multimorbidity adversely impacts the frequency of health service utilization.